1994
DOI: 10.1111/j.1476-5381.1994.tb14891.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cl channel blockers on Ca‐activated chloride and potassium currents in smooth muscle cells from rabbit portal vein

Abstract: 1 The effects of some chloride channel antagonists were studied on the calcium-activated chloride current (ICl(ca)) in smooth muscle cells from the rabbit portal vein with the perforated patch technique.2 4-Acetamido-4'-isothiocyanatostilbene-2,2'-disulphonic acid (SITS) and 4,4'-diisothiocyanato-stilbene-2,2'-disulphonic acid (DIDS) reduced the amplitude of spontaneous transient inward currents (STICs, calcium-activated 5 DIDS and SITS decreased the amplitude of IC1(ca) evoked by noradrenaline and caffeine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 26 publications
4
53
1
Order By: Relevance
“…Since niflumic acid increased the noradrenaline-evoked IK(Ca) without altering STOCs (spontaneous calcium-activated potassium currents) it is possible that this compound increases the evoked release of calcium from the intracellular store without altering the spontaneous release of calcium. It was observed previously that DIDS, SITS and A-9-C increased the evoked IvCac) (Hogg et, al., 1994) and it may be a general property of chloride channel blocking agents to enhance the amount of calcium released from the intracellular store.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Since niflumic acid increased the noradrenaline-evoked IK(Ca) without altering STOCs (spontaneous calcium-activated potassium currents) it is possible that this compound increases the evoked release of calcium from the intracellular store without altering the spontaneous release of calcium. It was observed previously that DIDS, SITS and A-9-C increased the evoked IvCac) (Hogg et, al., 1994) and it may be a general property of chloride channel blocking agents to enhance the amount of calcium released from the intracellular store.…”
Section: Discussionmentioning
confidence: 84%
“…Voltage-dependent effect of niflumic acid Previously we had demonstrated that A-9-C reduced STICs in a voltage-dependent manner whereas the inhibitory action of DIDS and SITS was not influenced by membrane potential (Hogg et al, 1994). We have carried out similar experiments with niflumic acid in potassium-free bathing and pipette solutions to eliminate STOCs which become prominent at potentials positive to -50 mV.…”
Section: Effect Of Niflumic Acid On Sticsmentioning
confidence: 99%
See 3 more Smart Citations